2020
DOI: 10.1021/acsptsci.9b00095
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin and the AT2 Receptor Agonist CGP42112 Evoked a Similar, Nonadditive, Cardiac Antifibrotic Effect in High Salt-Fed Mice That Were Refractory to Candesartan Cilexetil

Abstract: Fibrosis is involved in the majority of cardiovascular diseases and is a key contributor to end-organ dysfunction. In the current study, the antifibrotic effects of recombinant human relaxin-2 (serelaxin; RLX) and/or the AT 2 R agonist CGP42112 (CGP) were compared with those of the established AT 1 R antagonist, candesartan cilexetil (CAND), in a high salt-induced cardiac fibrosis model. High salt (HS; 5%) for 8 weeks did not increase systolic blood pressure in male FVB/N mice, but CAND treatment alone signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 80 publications
(193 reference statements)
4
15
0
Order By: Relevance
“…The level of collagen deposition induced by HS diets can vary between different mouse strains even without an elevation of blood pressure. We found that 5% HS diet for 8 weeks was able to increase cardiac fibrosis (by ~1.5‐fold using Picrosirius Red staining and hydroxyproline analysis) in FVB/N mice (Wang et al, 2020), whereas Le Corvoisier et al (2010) found a more than threefold increase in cardiac interstitial fibrosis using a similar protocol (4% HS diet for 8 weeks) in Swiss mice using the same methodology. Longer periods of 4% HS intake (e.g., 15 weeks) did not further increase interstitial fibrosis in the left ventricle (LV) of WKYs (Ferreira et al, 2010).…”
Section: Reactive Cardiac Fibrosis Modelsmentioning
confidence: 80%
See 2 more Smart Citations
“…The level of collagen deposition induced by HS diets can vary between different mouse strains even without an elevation of blood pressure. We found that 5% HS diet for 8 weeks was able to increase cardiac fibrosis (by ~1.5‐fold using Picrosirius Red staining and hydroxyproline analysis) in FVB/N mice (Wang et al, 2020), whereas Le Corvoisier et al (2010) found a more than threefold increase in cardiac interstitial fibrosis using a similar protocol (4% HS diet for 8 weeks) in Swiss mice using the same methodology. Longer periods of 4% HS intake (e.g., 15 weeks) did not further increase interstitial fibrosis in the left ventricle (LV) of WKYs (Ferreira et al, 2010).…”
Section: Reactive Cardiac Fibrosis Modelsmentioning
confidence: 80%
“…For example, 4% HS diet increased cardiac fibrosis in obese Zucker rats (Ali et al, 2015), Dahl salt‐sensitive (DSS) rats (Pushpakumar et al, 2013), as well as in the presence of Ang II (Gonzalez et al, 2015), and all these animals demostrated elevated blood pressure. However, the 4% HS‐induced cardiac fibrosis was not associated with increased blood pressure in Lewis rats (Pushpakumar et al, 2013), Swiss mice (Le Corvoisier et al, 2010) or FVB/N mice (Wang et al, 2020). Therefore, an appropriate salt concentration is essential for experimental design depending on whether blood pressure‐dependent or ‐independent remodelling is to be considered.…”
Section: Reactive Cardiac Fibrosis Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive Ang-[1–8] activity at the angiotensin type 1 receptor (AT 1 R) leads to hypertension, inflammation, atherogenesis, and tissue fibrosis ( 1 , 2 ). The angiotensin type 2 receptor (AT 2 R) plays a counter-regulatory role in AT 1 R actions, especially in the females ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…This class of endogenously generated mediators (and four generations of newer synthetic analogues with progressively increasing potency) promote the resolution of inflammation via the GPCR formyl peptide receptor-2 (FPR2), facilitating the healing process and restoration of tissue homeostasis in a range of settings of inflammation. The study reported by Wang et al describes the protective actions observed in response to the novel antifibrotic agent, relaxin, as well as to an angiotensin AT2 receptor agonist, alone and in combination, in a high salt diet model of cardiac fibrosis. These actions were accompanied by the blunting of cardiac inflammation but were independent of the lowering of blood pressure.…”
mentioning
confidence: 99%